The Role and Strategy of Islamic Higher Education in Improving Competence Student Face Revolution Industry Technology - Kardina Engelina Siregar (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2023)
The challenges faced by the world of education are increasingly complex, where education must be able to adapt to technological advances, integrate technology with human skills, and encourage innovations that can increase production system efficiency, flexibility, sustainability, and welfare. Therefore, Islamic Higher Education has a crucial role and strategy in dealing with current technological developments. This research aims to identify the roles and strategies of Islamic Universities in improving student competence in facing the technological revolution. The type of research used is a literature study, which is a technique of collecting data and information through literature review, including books, previous research, papers, journals, articles, as well as reports and magazines relevant to the research topic. The researcher records, understands, and classifies the literature related to this research. The results showed that the modernisation of character-based Islamic education is a must to create education that suits the needs of the millennial generation. Abstrak: Tantangan yang dihadapi dunia pendidikan semakin kompleks, di mana pendidikan harus mampu beradaptasi dengan kemajuan teknologi, mengintegrasikan teknologi dengan keterampilan manusia, dan mendorong inovasi yang dapat meningkatkan efisiensi sistem produksi, fleksibilitas, keberlanjutan, serta kesejahteraan. Oleh karena itu, Perguruan Tinggi Islam memiliki peran dan strategi yang krusial dalam menghadapi perkembangan teknologi saat ini. Penelitian ini bertujuan untuk mengidentifikasi peran dan strategi Perguruan Tinggi Islam dalam meningkatkan kompetensi mahasiswa dalam menghadapi revolusi teknologi. Jenis penelitian yang digunakan adalah studi kepustakaan, yang merupakan teknik pengumpulan data dan informasi melalui telaah literatur, termasuk buku, penelitian terdahulu, makalah, jurnal, artikel, serta laporan dan majalah yang relevan dengan topik penelitian. Peneliti melakukan pencatatan, pemahaman, dan klasifikasi literatur yang terkait dengan penelitian ini. Hasil penelitian menunjukkan bahwa modernisasi pendidikan Islam berbasis karakter menjadi keharusan untuk menciptakan pendidikan yang sesuai dengan kebutuhan generasi milenial.